Sistem Monitoring Energi Listrik 3 Fase Berbasis IoT dan Firebase - Muhtadi, M Zaky Zaim; Ranolat, Susana; Pujianto (Politeknik Negeri Malang, 2025)
This research develops an Internet of Things (IoT)-based three-phase electrical energy monitoring system using Firebase for real-time energy management at PEM Akamigas Campus. The system integrates PM1200 Schneider power meter, ESP32 microcontroller, RS485 to TTL converter, and Firebase Realtime Database to monitor electrical parameters (voltage, current, power) simultaneously across three phases. Implementation testing was conducted for two hours with two-minute intervals, demonstrating system reliability with 100% data transmission success rate and latency under 2 seconds. Results show power fluctuations ranging from 9177W to 26285W, with peak consumption of 26285W occurring at 16:00-16:28, correlating with campus operational patterns. Compared to previous research, this system offers advantages in simultaneous three-phase monitoring, scalable cloud integration, and the excellent processing capabilities of ESP32. Although the system relies on a Wi-Fi connection and is not equipped with predictive features, opportunities for further development include the integration of machine learning, notification systems, integration of building management systems, and expansion to multiple locations for sustainable smart campus energy management.